2014
DOI: 10.2217/epi.14.34
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifications in Prostate Cancer

Abstract: Prostate cancer is the most common cancer in men and the second leading cause of cancer deaths in men in France. Apart from the genetic alterations in prostate cancer, epigenetics modifications are involved in the development and progression of this disease. Epigenetic events are the main cause in gene regulation and the three most epigenetic mechanisms studied include DNA methylation, histone modifications and microRNA expression. In this review, we summarized epigenetic mechanisms in prostate cancer. Epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 80 publications
2
29
0
Order By: Relevance
“…Unfortunately, most of them still develop resistance, stressing that further development of medical interventions of CRPC is necessary. In the realm of PC epigenomics, extensive researches have been carried out in DNA methylation, histone modifications and microRNAs [41]. The enhancer related epigenomic studies, however, remain a gap in the field of PC research.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most of them still develop resistance, stressing that further development of medical interventions of CRPC is necessary. In the realm of PC epigenomics, extensive researches have been carried out in DNA methylation, histone modifications and microRNAs [41]. The enhancer related epigenomic studies, however, remain a gap in the field of PC research.…”
Section: Discussionmentioning
confidence: 99%
“…A full discussion of epigenomics as it relates to prostate cancer and BPH is beyond the scope of this review, interested readers are directed toward several reviews on the topic [6870]. There are numerous genes regulated by DNA methylation in prostate cancer [52,6871].…”
Section: Prostate Cancer and Benign Prostate Hyperplasia (Bph): A Reawamentioning
confidence: 99%
“…[58] DNA methylation—a major molecular mechanism of epigenetic changes—has been recognized as an important event in many cancer types, including lung cancer. [9,10] Studies have shown that gene methylation in the promoter regions regulates the silencing of tumor suppressor genes (TSGs), leading to the down-regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%